Enkulturasi Budaya: Pola Pewarisan Tradisi Menenun pada Generasi Muda di Desa Pringgasela Lombok Timur - Sukria Novianti; Muhammad Ruslan; Muhammad Khaerul Rizal; Muhammad Taupik Alfarizi; Jepri Utomo; Milla Noviana (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
The low interest of the younger generation in traditional crafts threatens the preservation of Nusantara textiles. A study entitled "Analysis of the Pattern of Traditional Weaving Heritage Transmission Among the Young Generation in Tenun Village, Pringgasela, East Lombok" aims to map the patterns of weaving skill transfer while identifying structural obstacles in the field. Through a descriptive qualitative method with a case study scheme, data were collected through participatory observation, documentation, and in-depth interviews with craftsmen across generations. The study results reveal that the transmission of cognitive knowledge is effective through the integration of passive enculturation in domestic spaces and non-formal community training. Nonetheless, the sustainability of this tradition is threatened by economic disincentives due to the low wages of Sesek cloth, which are uncompetitive with the modern sector, triggering young weavers to migrate as laborers after marriage. The implications of this research urge a total reform of the traditional craftsmen development pattern through strengthening the creative economy ecosystem and accelerating digital marketing literacy. This strategy is crucial to reduce the dominance of middlemen, increase partners' income, and foster the organic motivation of Gen Z in preserving Sasak cultural heritage.